HUBUNGAN PERSEPSI DAN SIKAP IBU NIFAS DENGAN MOBILISASI DINI POST SECTION CAESAREA DI RSIA ANNISA KOTA JAMBI - Kristy Mellya Putri (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
Early mobilization not performed by the post section caesarea mother resulted in longerhospitalization, which is more than 4 days and the wound healing process is slow. Anotherimpact caused by late mobilization is the occurrence of infection. This research is descriptivewith cross sectional approach, the population of this research are all postpartum caesareaRSIA Annisa of Jambi City that is 627, 40 samples of accidental sampling technique andunivariat and bivariate analyzed. The results of this study showed early mobilization of72.5%, good perception of 62.5% and a positive attitude of 55%. There is relation ofperception of postpartum mother with early mobilization of post section of caesarea at RSIAAnnisa Jambi City 2017 with p-value 0,008. There is no relationship of postpartum attitudewith early mobilization of post section of caesarea at RSIA Annisa Jambi City 2017 with pvalue0,270. For that it is expected that health workers pay attention in terms of providinggood food consumed during post-surgery, especially protein and vitamin intake, but alsomobilization guidelines need to be implemented according to the procedure for normalwound healing process.Keywords: Perception, attitude, early mobilization